أثر سياسة الدولة الإسلامي على توازن سوق السلع والخدمات: The Impact of The Islamic State’s Policy on The Balance of The Goods and Services Market - Al-Araimi, Khaloud Hamood Hamed; Mahyoub Murshed, Amer Abdulwahab; Md Rasip, Osman (Journal Al-Muqaddimah, 2023)
This article seeks to elucidate the impact of the Islamic state’s intervention policy on achieving national economic equilibrium. The study aims to explore the overall legal policies of Islamic state intervention throughout its history, their effect on the balance of goods and services markets. The study addresses the complexity of current economic reform policies, emphasizing the significance of shedding light on the Islamic system and its legitimate paths in providing solutions for stabilizing national economic markets, particularly the goods and services market. Employing a descriptive-analytical approach, the study reveals several conclusions, including the Islamic state’s duty to protect its communities, encompassing not only matters of faith and worship but also safeguarding the wealth and natural resources of Muslims. The study underscores the necessity of implementing structural reforms in the goods and services market, emphasizing their positive impact on economic activity and growth. It highlights the greatness of the Islamic economic system, distinguishing it from contemporary economic systems, emphasizing Islam’s comprehensive nature, covering all aspects of life, including economics, administration, governance, and politics.